Role Of Truecaller Application In Preventing Phone Call And Text Message Scams - Indriyani; Dewi Aprinia (Institute of Computer Science (IOCS), 2022)
Increased technological advancement must be accompanied by an increase in the potential for technology abuse. It is easier for criminals to commit crimes in today's modern and sophisticated civilization using increasingly advanced technology. Scam by telephone, text message, or other forms of communication is an example of a prevalent technologically-based criminal. This study aims to investigate the role of the blocking application for calls and text messages, especially the Truecaller application, given the prevalence of telephone and text messaging fraud and crime. This research focuses mainly on the efficiency of Truecaller's features and the application's popularity among the wider public.